Enhancing Early Childhood Gross Motor Skills Through Modified Jumping Games - hasanah, Nur; kuswanto, Cahniyo Wijaya (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2025)
This study aims to improve gross motor skills in early childhood through modifications to various jumping games. Technological developments have contributed to a decline in children’s physical activity, which consequently affects their motor development. Traditional jumping games, which can enhance balance, agility, and coordination, are increasingly being replaced by digital games. This study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model in two cycles, involving 20 children aged 5–6 years. Modifications were made to the game by adjusting the rules and equipment to increase children's engagement. The quantitative findings show an increase in gross motor skill scores from 1.5 (Emerging stage or beginning to develop) in Cycle 1 to 3.3 (Expected Level of Development or very well developed) in Cycle 2. This improvement was significant, with all children actively participating in the activities, indicating that the game modifications had a positive and comprehensive impact on various aspects of gross motor skills. The study highlights the importance of modifying traditional games as an effective strategy to increase physical activity and support children's motor development in the digital age.